(3eMGVQGJ aj GdeQGLYI hJObjb GdMSGHGJs - (3YHO GdbGOQ (B, (3HhYRI s ((3GdLRGFQ(B:s (3OGQ GdcJGH GdYQHj(B,s, 2022)
(3gPG GdcJGH jbOe eLehYI eMGVQGJ aj eGOI GdeQGLYI hGdJObjb GdVQjHj, hPdc dJRhjO GdWGdH hGdHGMK HCge GdeYGQa GdCSGSjI hGdeaGgje hGdeUWdMGJ GdfXQjI hGdJWHjbjI ddeQGLYI hGdJObjb GdVQjHj, HGdEVGaI Edi GdJYQV ddLGfH GdELQGFj GdeYehd Hg YedjkG deeGQSI GdeQGLYI hGdJObjb GdVQjHj aj GdeDSSGJ hYdi eSJhi GdEOGQGJ GdVQjHjI aj GdLRGFQ(B. (3ehLg dWdHI GdeGSJQ aj TYHI GdYdhe GdeGdjI hGdeMGSHI, GdCcGOjejjf hGdeJYGedjf GdGbJUGOjjf Gdegfjjf hLejY GdHGMKjf hGdegJejfs
(3GdeQGLY U(B.182s
Keywords: (3GdJObjb GdLHGFjs; (3GdeQGLYIs